The Role Of Teachers In Training The Independence Of Children Aged 4-5 Years In Group A Of Tkn Pembina Dewi Kayangan In The 2024/2025 Academic Year - Neni Yulia; Muhammad Muhajirin; Muh. Hamdani (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of this study is to determine the role of teachers in training the independence of children aged 4-5 years at TKN Pembina Dewi Kayangan, as well as to determine how teachers play a role in training children's independence. The study was conducted at TKN Pembina Dewi Kayangan in Karang Lande Village, Kayangan Subdistrict, Kayangan District, KLU, with a total of 4 students, consisting of 7 boys and 8 girls. The research method used was a descriptive qualitative approach, a research methodology that focuses on a deep understanding of phenomena in their natural context. The research used Milles Hubberman's data analysis method, which consists of four stages: data condensation, data display, drawing conclusions, and verifying conclusions.The results of this study at the Dewi Kayangan State Kindergarten indicate that the development of independence among children in Group A (ages 4–5) has shown significant progress through a structured approach that includes routine activities, positive reinforcement, and direct modeling by teachers. The children were able to achieve physical independence (such as tidying up toys and eating independently), emotional independence (expressing needs), social independence (interacting with peers), cognitive independence (decision-making), and responsibility through the daily task program. Despite challenges such as individual developmental variations, teacher-child ratio limitations, and the influence of parenting styles at home, collaboration between schools and parents, along with a conducive learning environment, has successfully established a strong foundation for independence. These findings also emphasize the importance of consistent methods, differentiated approaches, and the optimization of supportive resources for more holistic and inclusive independence development in young children.